Framework of solutions for improvement of Vietnam Global Innovation Index - Mai, Nguyen Thi Phuong; Linh, Phan Xuan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2020)
Global Innovation Index (GII) is a tool set for assessing and ranking innovation capacities of nations or economic sectors. GII Index is co-published by INSEAD (France), WIPO and Cornell University (USA) annually for this purpose since 2007. By 2017, the Government of Vietnam had used the results by GII for the first time and decided the objective to improve Vietnam GII Index for measuring outcomes of enhancement of the national innovation capacity (Resolution No. 19/2017/NQ-CP by the Government on 06 February 2018). The Government assigned line ministries and organizations to take leads and coordination for improvement of each GII indicator. In practice, GII is a set of synthetic indicators and, with National Innovation System (NIS) approach, covers multiple fields and sectors. This approach remains a little novel in Vietnam then not easy for related units to set up measurements for improvement. This paper provides an analysis of strong and weak points of Vietnam GII Index as well as existing policy solutions. On basis of that a proposal of global nature is made for possible improvement of Vietnam GII Index as indicated by the Government. Code: 20012001 <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">